Review of the development of the hydrogen maser technique and a brief introduction to its space applications - Dai, Jiayu; Liu, Tiexin; Cai, Yong; Chen, Zhichun; Li, Qi (Frontiers in Physics, 2022)
Since 1960, when the first hydrogen frequency standard, the microwave amplification by stimulated emission of radiation (maser), was developed in the laboratory of Norman Ramsey at Harvard University, the performance of its frequency stability and technique development have been closely related to scientific research. A variety of H-maser designs have been developed for the demands of space science applications, including the deep space network (DSN) and the gravity probe (GP) experiment. H-maser is one of three well-developed microwave atomic frequency standards and is widely used worldwide in both ground and on-board-based settings. Along with upgrades to the frequency stability performance of the H-maser, improved knowledge of the world has also been reported.